DINAMIKA KEHIDUPAN MINORITAS MUSLIM DI BALI - Indriana Kartini (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2011)
The history of Islam can be traced back almost in all regencies in Bali, suchas Denpasar City, Badung, Buleleng, Jembrana, Gianyar, Tabanan, Bangli,Karangasem and Klungkung. In this regard, the existence of Balinese Muslimhas also enriched the discourse of Islam-Hindu society in Bali. The relationship between Balinese Muslim and Hindu communities is relatively harmonic since the Kingdom era, despite some social and economic problems between both communities. This article examines the dynamics of Balinese Muslim community in some regencies. It analyses how Balinese Muslim build and preserve their religious identity in the middle of Hindu majority. In addition, this article examines the dynamics of relationship between Balinese Muslim and Hindu, including some problems faced by Balinese Muslims regarding the implementation of Ajeg Bali discourse. The social and economic problems are not only big challenges for Balinese Muslim and Hindu community to respect, understand and shared, but also for local government to solve those problems together with both communities. The latter may preserve unity between religious communities in Bali which has been built up since hundred years ago. This article recommends that local government policies should not only considered majority rights but also considered minority rights of Balinese Muslims.Keywords: minority, ethnicity, identity, collective discrimination